The Effect of Profitability, Liquidity, Leverage, Firm Size, Operating Capacity, and Retained Earnings Towards Financial Distress: Evidence from Energy Companies - Fatimah Adityaningrum; Mei Nia Widyaningrum; Mahirun Mahirun (Universitas Trunojoyo Madura, 2024)
This research aims to anticipate the possibility of financial distress by analyzing fundamental company financial factors such as profitability, liquidity, leverage, firm size, operating capacity and retained earnings ratio, specifically in energy sector companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research carried out is causal associative research. This research data uses secondary quantitative panel data. The population in this study are energy companies listed on the Indonesia Stock Exchange in the 2018-2022 period. This sector was selected due to indications that energy companies were facing financial difficulties during the pandemic, as evidenced by several energy companies being delisted from the stock exchange. The sampling technique used was purposive sampling, obtaining 58 companies as research samples with five years of observation, resulting in 290 total observation data. The technique used for analysis is logistic regression with the help of EViews 13 software. The results of this study show that liquidity, firm size, and retained earnings hurt financial distress, while leverage has a positive effect on financial distress. Meanwhile, profitability and operating capacity do not affect financial distress. This research provides empirical evidence about the factors that influence financial distress and contributes to the signaling theory application literature in predicting bankruptcy conditions through financial distress analysis. Thus, this research could be a consideration for stakeholders when making decisions.